Exploring Social Influences on Self-Identity Formation through English Language Proficiency - Delviana Iloponu; Hanisa Hanafi; Muziatun (Transbahasa, 2025)
This research aims to explore the social influences on self-identity formation through English language proficiency, utilizing a qualitative approach. English proficiency plays a significant role in forming individuals’ self- identity, particularly amid the academic enivourment. The study involved a questionnaire distributed to 20 students major of English Language Education Program in Gorontalo state university students from diverse social backgrounds and varying levels of English proficiency. Data analysis was conducted using a thematic approach to identify key patterns and themes that illustrate the impact of social factors on the identity formation process. The findings indicate that social environments, including peers, and educational institutions, play an essential role in shaping how individuals perceive themselves through the lens of their English language abilities. However, family factor not significant forming student’s self-identity, because they do not have an educational background or understanding of English. These findings are expected to provide deeper insights into the role of English proficiency in self-identity formation and this research provides significant benefits for educational institutions in understanding their strategic role in shaping students' self-identity.